2013
DOI: 10.1111/eea.12091
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of necrotrophic and biotrophic plant pathogens on the aphid Aphis fabae

Abstract: Phytophagous insects have to contend with a wide variation in food quality brought about by a variety of factors intrinsic and extrinsic to the plant. One of the most important factors is infection by plant pathogenic fungi. Necrotrophic and biotrophic plant pathogenic fungi may have contrasting effects on insect herbivores due to their different infection mechanisms and induction of different resistance pathways, although this has been little studied and there has been no study of their combined effect. We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…Current thinking often states that while the pathway involving salicylic acid (SA) is usually induced by and effective against biotrophic pathogens and sucking herbivores (Ali and Agrawal , Thaler et al. , Al‐Naemi and Hatcher ), necrotrophic pathogens and chewing herbivores principally activate and negatively respond to the jasmonic acid (JA) pathway (Ali and Agrawal , Thaler et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current thinking often states that while the pathway involving salicylic acid (SA) is usually induced by and effective against biotrophic pathogens and sucking herbivores (Ali and Agrawal , Thaler et al. , Al‐Naemi and Hatcher ), necrotrophic pathogens and chewing herbivores principally activate and negatively respond to the jasmonic acid (JA) pathway (Ali and Agrawal , Thaler et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…, Ali and Agrawal , Thaler et al. , Al‐Naemi and Hatcher ). Given these specificities, we predict that the response of herbivores to plant infection by fungi will depend interactively on fungus lifestyle and herbivore feeding guild, with stronger negative effects of necrotrophic fungi on chewing than on sap feeding insects, but conversely more negative effects of biotrophic fungi on sap feeding insects.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pathogen effects on plant resistance to insects will depend on the biology of the herbivore, e.g., whether it is a phloem feeder or a chewing larva [19]. For example, the necrotrophic pathogen Botrytis cinerea inhibited the development, fecundity and survival rate of the aphid Aphis fabae in Vicia faba, whereas the biotrophic fungus Uromyces viciae-fabae enhanced aphid performance [21]. Most interestingly, the effect of combined B. cinerea and U. viciae-fabae stress on aphid performance seemed to fluctuate depending on the order of infection [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the necrotrophic pathogen Botrytis cinerea inhibited the development, fecundity and survival rate of the aphid Aphis fabae in Vicia faba, whereas the biotrophic fungus Uromyces viciae-fabae enhanced aphid performance [21]. Most interestingly, the effect of combined B. cinerea and U. viciae-fabae stress on aphid performance seemed to fluctuate depending on the order of infection [21]. In contrast, B. cinerea pretreatment had no significant effect on further performance of Pieris rapae caterpillars in Arabidopsis [22].…”
Section: Introductionmentioning
confidence: 99%
“…The interactions of phytopathogenic fungi and insect herbivores on shared host plants can have a variety of outcomes (10). It has been hypothesized that necrotrophs, such as F. graminearum (11), consistently reduce the fitness of insects feeding on the infected host, although there is evidence contradicting this claim (12,13). It has also been shown that insect herbivory of hosts indirectly causes changes to plant chemistry, biochemistry, physiology, and growth (14) in such a way as to alter the host's capacity to withstand secondary infection.…”
mentioning
confidence: 99%